2006
DOI: 10.1111/j.1440-1681.2006.04334.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cardiotoxin Iii‐induced Apoptosis in Human Colorectal Cancer Colo205 Cells

Abstract: Cardiotoxin III (CTX III) is a basic polypeptide with 60 amino acid residues isolated from Naja naja atra venom. This is the first report on the mechanism of the anticancer effect of CTX III in human colorectal cancer Colo205 cells. 2. Cardiotoxin III-induced Colo205 cell apoptosis was confirmed by DNA fragmentation (DNA ladder and sub-G1 formation) with an IC(50) of 4 mg/mL at 48 h. 3. Further mechanistic analysis demonstrate that CTX III induced the loss of mitochondrial membrane potential (Dym), cytochrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 37 publications
0
17
0
1
Order By: Relevance
“…Western blotting demonstrated that PSⅠ treatment dose-dependently up-regulated the expression of Bax and down-regulated the expression of Bcl-2, indicating that the modulation of Bcl-2 and Bax was critical for PSⅠ-induced apoptosis of SGC7901 cells. Indeed, Bax accelerated the release of the apoptosis-inducing factor cytochrome c from the mitochondria, thus activating the caspase cascade [28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting demonstrated that PSⅠ treatment dose-dependently up-regulated the expression of Bax and down-regulated the expression of Bcl-2, indicating that the modulation of Bcl-2 and Bax was critical for PSⅠ-induced apoptosis of SGC7901 cells. Indeed, Bax accelerated the release of the apoptosis-inducing factor cytochrome c from the mitochondria, thus activating the caspase cascade [28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous heat-stable neurotoxins and cardiotoxins -obtained from venoms of different cobra species -were already detected and structurally studied (3). Some of them presented anticancer potential, some antinociceptive properties and others even inhibited bone resorption (4,18,(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Although some anticancer drugs such as doxorubicin, anthracyclines, and trastuzumab have the well-known cardiotoxicity [10, 11], CTXIII was found to exhibit a variety of bioactivities with anticancer potential. For example, we previously found that CTXIII inhibits the cellular proliferation and induces apoptosis of various cancer cells, including breast cancer [12], leukemia cells [13], colorectal cancer [14], and oral cancer [15, 16]. …”
Section: Introductionmentioning
confidence: 99%